2021
DOI: 10.3390/diagnostics11040689
|View full text |Cite
|
Sign up to set email alerts
|

Non-Alcoholic Fatty Liver Disease and Cardiovascular Comorbidities: Pathophysiological Links, Diagnosis, and Therapeutic Management

Abstract: Non-alcoholic fatty liver disease (NAFLD) has a growing prevalence in recent years. Its association with cardiovascular disease has been intensively studied, and certain correlations have been identified. The connection between these two entities has lately aroused interest regarding therapeutic management. In order to find the best therapeutic options, a detailed understanding of the pathophysiology that links (NAFLD) to cardiovascular comorbidities is needed. This review focuses on the pathogenic mechanisms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
1
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 224 publications
(241 reference statements)
0
19
1
3
Order By: Relevance
“…Although genetic factors also play a pivotal role in the development of NAFLD, a major contribution to its pathogenesis is attributed to modifiable risk factors, i.e., obesity, metabolic syndrome, and diabetes ( 2 , 3 ). As patients diagnosed with NAFLD are prone to developing liver cirrhosis as well as hepatocellular carcinoma, urgent measures are needed to combat the spread of the NAFLD epidemic ( 4 7 ), particularly as there are no approved pharmacotherapies for this chronic hepatic disorder.…”
Section: Introductionmentioning
confidence: 99%
“…Although genetic factors also play a pivotal role in the development of NAFLD, a major contribution to its pathogenesis is attributed to modifiable risk factors, i.e., obesity, metabolic syndrome, and diabetes ( 2 , 3 ). As patients diagnosed with NAFLD are prone to developing liver cirrhosis as well as hepatocellular carcinoma, urgent measures are needed to combat the spread of the NAFLD epidemic ( 4 7 ), particularly as there are no approved pharmacotherapies for this chronic hepatic disorder.…”
Section: Introductionmentioning
confidence: 99%
“…Non-alcoholic fatty liver disease (NAFLD) encompasses a set of pathologies associated with ectopic lipid accumulation in hepatocytes [ 1 ]. NAFLD can progress to non-alcoholic steatohepatitis (NASH), an inflammatory condition which is increasing in prevalence in parallel with other diseases connected to lipid metabolism, such as type 2 diabetes and cardiovascular disease [ 2 ]. NASH is characterized by hepatic necrosis, increased inflammatory signaling, immune cell infiltration, and the potential to progress to fibrosis, cirrhosis, hepatocellular carcinoma, and ultimately liver failure [ 1 , 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…The authors concluded that this "liver-sparing" phenomenon might be linked with the elevated cardiovascular risk of offspring born from these pregnancies [91]. Moreover, liver and cardiovascular disorders seem to share pathophysiological links also in adulthood, as previously reviewed by Jichitu et al (2021) [92]. More recently, Opheim et al (2020) revealed that the blood flow to the fetal liver was negatively associated with the maternalfetal gradient of glucose and positively associated with the fraction of blood shunted via the ductus venosus in pregnant females with a normal BMI but not in those suffering from overweight.…”
Section: Fetal Liver Length Measurements By Ultrasound-any Value?mentioning
confidence: 76%
“…Overall, the analyzed research papers point out a possible connection between fetal liver indices and GDM; however, the base of evidence is too small to conclude that these parameters can serve as predictors of GDM in pregnancy. Consequently, further research is needed to clarify the relationship between fetal liver indices and GDM and, if our hypothesis is confirmed, to delineate cutoff values for the variables that could predict the development of GDM [5,24,37,68,69,[85][86][87][88][89][90][91][92][93]. Only one study, conducted by Perovic et al (2014), proposed an FLL of 39 mm as a predictor of GDM [37].…”
Section: Fetal Liver Length Measurements By Ultrasound-any Value?mentioning
confidence: 87%
See 1 more Smart Citation